'Human trafficking, public health and the law': a comprehensive analysis of intersections. - Haase, Elisabeth (Journal of Public Health: From Theory to Practice (2198-1833), 2014)
Aim: The extraordinary topic of 'Human Trafficking, Public Health and the Law' was subject of an interdisciplinary and international Spring School that took place in March 2013 in Italy. The aim of the meeting was a comprehensive examination of the human trafficking issue. Subject and methods: In collaboration with seven expert lecturers, a group of students particularized the issues and claims related to human trafficking and public health from the angles of all relevant disciplines. Past legal decisions were evaluated in order to recommend future solutions in the common interest with respect to human dignity. Results: The main outcome of the two weeks of lectures, group work and a field trip are practical approaches and the document: Siena Principles on Human Trafficking and Public Health. Conclusion: The costs for society that arise due to the adverse effects of human trafficking encompass the degradation of human rights, poor public health, weakened social development, and disturbed communities. Human trafficking therefore is a critical health issue with serious social implications that requires both medical and legal attention.